Prognostic Biochemical Markers in Traumatic Brain Injury: Which One is The Best? - Juwita Juwita Juwita; Hidayaturrahmi Hidayaturrahmi Hidayaturrahmi; Muhammad Ansari Adista; Khairunnisa Khairunnisa Ichwan (JURNAL IMPLEMENTA HUSADA, 2024)
Traumatic brain injury is significant cause of disability and mortality; most of the patient are young and productive. The Glasgow Coma Scale (GCS) is a common tool for classifying the injury, while imaging is used to diagnose. However, those modalities have limitations, which is mild to moderate brain injury due to the brain parenchymal changes cannot be found on imaging. Currently, several marker proteins (biochemical markers) of body fluids such as cerebrospinal fluid, blood or urine have been studied and are specific enough and easily accessible for classification and predict prognosis of traumatic brain injury. Biochemical markers which are widely used, considered effective and accurate for diagnosis and prognosis brain injury are S100β, GFAP, neuron-specific enolase (NSE), and tau. This study will describe and compare the characteristics and role of each of these marker proteins.